Current status of intravenous tissue plasminogen activator dosage for acute ischaemic stroke: an updated systematic review. Issue 1 (13th January 2018) - Wang, Xia; You, Shoujiang; Sato, Shoichiro; Yang, Jie; Carcel, Cheryl; Zheng, Danni; Yoshimura, Sohei; Anderson, Craig S; Sandset, Else Charlotte; Robinson, Thompson; Chalmers, John; Sharma, Vijay K
Abstract : The optimal dose of recombinant tissue plasminogen activator (rtPA) for acute ischaemic stroke (AIS) remains controversial, especially in Asian countries. We aimed to update the evidence regarding the use of low-dose versus standard-dose rtPA. We performed a systematic literature search across MEDLINE, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), PsycINFO and Cumulative Index to Nursing and Allied Health Literature (CINAHL) from inception to 22 August 2016 to identify all related studies. The outcomes were death or disability (defined by modified Rankin Scale 2–6), death, and symptomatic intracerebral haemorrhage (sICH). Where possible, data were pooled for meta-analysis with ORs and corresponding 95% CIs by means of random-effects or fixed-effects meta-analysis. We included 26 observational studies and 1 randomised controlled trial with a total of 23 210 patients. Variable doses of rtPA were used for thrombolysis of AIS in Asia. Meta-analysis shows that low-dose rtPA was not associated with increased risk of death or disability (OR 1.13, 95% CI 0.95 to 1.33), or death (OR 0.86, 95% CI 0.74 to 1.01), or decreased risk of sICH (OR 1.06, 95% CI 0.65 to 1.72). The results remained consistent when sensitivity analyses were performed including only low-dose and standard-dose rtPA or only Asian studies. Our review shows small difference between the outcomes or the risk profile in the studies using low-dose and/or standard-dose rtPA for AIS. Low-dose rtPA was not associated with lower risk of death or disability, death alone, or sICH.